A genotyping protocol for multiple tissue types from the polyploid tree species Sequoia sempervirens (Cupressaceae)1. (9th March 2015) - Narayan, Lakshmi; Dodd, Richard S.; O'Hara, Kevin L.
Abstract : Premise of the study: Identifying clonal lineages in asexually reproducing plants using microsatellite markers is complicated by the possibility of nonidentical genotypes from the same clonal lineage due to somatic mutations, null alleles, and scoring errors. We developed and tested a clonal identification protocol that is robust to these issues for the asexually reproducing hexaploid tree species coast redwood ( Sequoia sempervirens ). Methods: Microsatellite data from four previously published and two newly developed primers were scored using a modified protocol, and clones were identified using Bruvo genetic distances. The effectiveness of this clonal identification protocol was assessed using simulations and by genotyping a test set of paired samples of different tissue types from the same trees. Results: Data from simulations showed that our protocol allowed us to accurately identify clonal lineages. Multiple test samples from the same trees were identified correctly, although certain tissue type pairs had larger genetic distances on average. Discussion: The methods described in this paper will allow for the accurate identification of coast redwood clones, facilitating future studies of the reproductive ecology of this species. The techniques used in this paper can be applied to studies of other clonal organisms as well.